Risks of angled implant placement on posterior mandible buccal/lingual plated perforation: A virtual immediate implant placement study using CBCT - Tian-You Wang; Po-Jan Kuo; Earl Fu; Hsin-Yu Kuo; Nancy Nie-Shiuh Chang; Min-Wen Fu; E-Chin Shen; Hsien-Chung Chiu (Elsevier, 2019)
Background/purpose: Immediate implant placement has been considered to be a successful treatment procedure. The bone plate perforation (BPP) may be one of severe complication and potentially life-threatening situation. The aim of this virtual study is to evaluate the influences of angled implant insertion on BPP during immediate implant installation in the posterior mandible. Materials and methods: Cone beam computed tomography images of 488 posterior teeth from 61 patients were selected. Virtual immediate implant placement (VIIP) was performed at each posterior tooth following the appropriate axis with the prosthetic-driven planning and different deviation angles of 3-, 6-, or 9-degree. BPP was then examined from cross-sectional images obtained. Furthermore, the relation of lingual bony morphology and BPP were also determined. Results: The incidence of buccal and lingual BPP increased as the deviation angle increased in posterior mandible area. Incidence of lingual BPP was significantly influenced by angular deviation and type of lingual bony morphology after adjusting for age, gender, tooth type, and right/left side. An increase in incidence odds of over 6-fold (OR = 6.583) was noted for placements angled by 9° compared with placements made without angulation, and an increase in incidence odds of over 3-fold (OR = 3.622) was noted for teeth with the undercut-type lingual morphology compared with the other types. Conclusion: The present Results indicate that accurate selection of the implant insertion angle and full awareness of the bony anatomy at the implant recipient site are essential to prevent BPP in the posterior mandible. Keywords: Complication, Dental implant, Mandible, Anatomy, Cone beam computed tomography